Exigência de treonina e triptofano digestível para codornas de corte - Ton, Ana Paula Silva (2010)
Four studies were carried out to estimate the nutritional requirements of digestible threonine and tryptophan for growing meat quail (Coturnix coturnix sp). In the first experiment, the objective was to estimate the requirements of digestible threonine from 1 to 14 days of age, using 1,350 meat quail distributed in a completely randomized design, with six levels of digestible threonine (1.08; 1.15; 1.22; 1.29; 1.36 and 1.43% of diet), five replications and 45 quail per experimental unit. The feed intake (FI), the weight gain (WG) and body weight (BW) showed a quadratic effect, estimating 1.26% of digestible threonine (DThr) in diet. The threonine intake showed estimative of 1.34% of digestible threonine according to the LRP (Linear Response Plateau) model. The protein deposition rate (PDR) in carcass and carcass energy retained (CER) showed quadratic effect, estimating the levels of 1.18 and 1.20% of digestible threonine. The small intestine morphometry showed a cubic effect, estimating 1.16, 1.13 and 1.14% of digestible threonine. There was a linear increase in feed cost per kilogram of body weight gain with increasing levels of digestible threonine. It was concluded that the requirement for maximum growing of meat quail is 1.26% of digestible threonine in diet, corresponding to the Digestible Lysine (DL):DThr ratio of 67.02. In the second experiment, the objective was to estimate the requirements of digestible threonine from 15 to 35 days of age, using 1,020 meat quail, distributed in a completely randomized design, with six levels of digestible threonine (0.93; 1.00; 1.07; 1.14; 1.21 and 1.28% of diet), five replications and 34 quail per experimental unit. The crypt depth of duodenum and jejunum showed quadratic effect estimating of 1.09 and 1.19% of digestible threonine in the diet. There was a linear increase in ileum villus height, in threonine intake and in feed cost per kilogram of body weight gain with increasing levels of digestible threonine. The nutritional requirement for maximum growth of meat quail is 0.93% of digestible threonine in diet, corresponding to the DL:DThr ratio of 53.76. In the third experiment, the objective was to estimate the requirements of digestible tryptophan from 1 to 14 days of age, using 1,950 meat quail distributed in a completely randomized design, with six levels of digestible tryptophan (0.27; 0.30; 0.33; 0.36; 0.39 and 0.42% of diet), five replications and 65 quail per experimental unit. There was an increase of FI, tryptophan intake (TI), WG and BW with the digestible tryptophan (DTrp) levels increase. The level of ash (LA) had a linear decrease with the digestible tryptophan levels increase. The fat deposition rate (FDR), PDR and CER showed a quadratic effect, with estimative of 0.35 and 0.34% of digestible tryptophan on diet for maximum deposition. There was a linear increase in diet cost per kilogram of body weight gain with the digestible thyptophan levels increase. The nutritional requirement for maximum growth of meat quail is greater or equal to 0.42% of digestible tryptophan in diet, corresponding to the DL:DTrp ratio of 22.34. In the fourth experiment, the objective was to estimate the requirements of digestible tryptophan from 15 to 35 days of age, using 1,350 meat quail, distributed in a completely randomized design, with six levels of digestible tryptophan (0.22; 0.25; 0.28; 0.31; 0.34 and 0.37% of diet), five replications and 45 quail per experimental unit. There was an increase of TI, carcass yield, LA and PDR 35 days of age with the digestible tryptophan levels increase. The nitrogen balance (NB) and metabolization coefficient (MC) increased linearly with the digestible tryptophan levels increase. There was a linear increase in diet cost per kilogram of body weight gain with the digestible thyptophan levels increase. The nutritional requirement for maximum growth of meat quail is 0.22% of digestible tryptophan in diet, corresponding to the DL:DTrp ratio of 12.72. It was concluded that meat quail have a higher nutritional requirement for digestible threonine and tryptophan for maximum performance in the initial phase of growth, 1 to14 days of age, compared to the late growth phase of 15 to 35 days of age.